Accounting Ethics Education on Ethical Behaviour of Accounting Graduates in Malaysia - Fatin Arissa Parsimin; Zalailah Salleh; Dato' Hasnah Hj Haron; Nurul Nazlia Jamil; Nathasa Mazna Ramli (USIM Press, 2024)
Vol. 20, No. 2